2015
DOI: 10.1038/bjc.2015.170
|View full text |Cite
|
Sign up to set email alerts
|

miR-9-3p plays a tumour-suppressor role by targeting TAZ (WWTR1) in hepatocellular carcinoma cells

Abstract: Background:The inactivation of the Hippo pathway lead to TAZ (PDZ-binding motif)/YAP (yes-associated protein) overexpression, and is associated with worse prognostic outcomes in various cancers including hepatocellular carcinoma (HCC). Although there are several reports of microRNA (miR) targeting for YAP, miR targeting for TAZ remains unclear. The aim of this study is to identify the miR targeting TAZ expression in HCC.Methods:MicroRNA expression was analysed using the Human miFinder 384HC miScript miR PCR ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 33 publications
8
66
1
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Depending on the Hippo pathway component that is targeted, this can up- or down-regulate YAP/TAZ activity. miR-9-3p has been reported to specifically target TAZ in hepatoma cell lines 95 , an activity which will need to be validated in vivo . Several other microRNAs to be considered with respect to the liver include LATS2 targeting miR-135b 96 and miR-31 97 , and miR-375 which regulates YAP1 98 .…”
Section: Mechanisms That Moderate Yap/taz Activitymentioning
confidence: 99%
“…TAZ is an important transactivator of the Hippo pathway in liver cancer cells 95, 109 , although there has been no in-depth study to determine the specific roles for YAP and TAZ in the liver. Several genome-wide, chromatin immunoprecipitation studies of YAP and TAZ binding found these molecules to be interchangeable, binding to the same sites across the genome and presumably regulating the expression of similar genes 14, 15 .…”
Section: Liver Cancer Developmentmentioning
confidence: 99%
“…For instance, miR-9 expression was recently reported to be significantly upregulated in non-small-cell lung cancer (NSCLC) tissues, which further promoted the growth of NSCLC cells and decreased the growth inhibitory effect of erlo-tinib 17. In contrast, miR-9 played a suppressive role by targeting TAZ in hepatocellular carcinoma cells 18. Recently, several studies revealed that miR-9 was involved in the pathogenesis of MM.…”
Section: Introductionmentioning
confidence: 99%